PENINGKATAN HASIL BELAJAR SISWA MELALUI METODE COOPERATIVE INTEGRATED READING AND COMPOSITION DALAM PEMBELAJARAN PKn DI SEKOLAH DASAR - Merliena Qodrio; Darnis Arief; Abna Hidayati (Universitas Pahlawan Tuanku Tambusai, 2019)
This study was motivated by the lack of student learning outcomes in teaching civics, and the lack of media are used to help the learning process. The purpose of this study was to describe the learning outcomes of students in class V SD Shabbihisma 1 Padang by using the method of Cooperative Integrated Reading and Composition on civics lesson. This type of research is classroom action research conducted in two cycles, the subject of this research is class V SD Shabbihisma 1 Padang, amounting to 27 people. The research instrument used in this study is, teacher observation sheet activities, observation sheet the students' attitudes (affective), student behavior observation sheets (psychomotor) and test student learning outcomes. The results showed that the cognitive learning in silkus I is 60.52% increased to 86.29% in the second cycle, namely affective assessment, the assessment of students in response to a joint decision on the determination of the duty cycle I is 63.37% increased to 83, 92% in the second cycle and psychomotor assessment that behavioral assessment of students in carrying out the responsibility in the first cycle is 67.53% increased to 82.65% in the second cycle. Based onthis study concludedthat byusing themethod ofCooperative IntegratedReadingandCompositioncanimprove student learning outcomes. Researcherssuggest thatteachers canusemethodsCooperative IntegratedReadingandCompositionas an alternativeincivicslearningfor learningfunandnotmake studentsbored.